Evaluation of hybrid neutralization/biosorption process for zinc ions removal from automotive battery effluent by dolomite and fish scales - Ribeiro, C (Environmental technology, 2019)
This work focused in the evaluation of Oreochromis niloticus fish scales (FS) as biosorbent material in the removal of Zn from a synthetic effluent based on automotive battery industry effluent and, further, a hybrid neutralization/biosorption process, aiming at a high-quality treated effluent, by a cooperative use of dolomite and FS. For this, a physicochemical and morphological characterization (i.e. SEM-EDX, FTIR, XRD, and TXRF) was performed, which helped to clarify a great heterogeneity of active sites (phosphate, carbonate, amide, and hydroxyl) on the biosorbent; also the inorganic constituents (apatites) leaching from the FS was identified. Biosorption results pointed out to a pH-dependent process due to changes in the functional group's anionic character (i.e. electrostatic interactions), where an initial pH = 3 favored the Zn uptake. Kinetic and equilibrium studies confirmed the heterogeneous surface and cooperative sorption, wherein experimental data were described by Generalized Elovich kinetic model and the favorable isotherm profile by Langmuir-Freundlich isotherm ( qmax  = 15.38 mg g-1 and 1/n>1 ). Speciation diagram of Zn species along with the leached species demonstrated that, for the studied pH range, the biosorption was the most likely phenomena rather than precipitation. Finally, the hybrid neutralization/biosorption process showed great potential since both the Zn concentration levels and the pH reached the legislation standards (CZn = 4 mg L-1; pH = 5). Hence, based on the characterization and biosorption results, a comprehensive evaluation of the involved mechanisms in such complex system helped to verify the prospective of FS biosorbent for the Zn treatment from solution, in both individual and hybrid processes